Assessment of remineralization potential of Theobromine and Sodium Fluoride gels on Artificial Caries like lesions - Elsherbini, Mohamed Saber (Brazilian Dental Science, 2020)
Objective: To compare the remineralization potential of theobromine and sodium fluoride gels on artificial caries like lesion. Materials and Methods: Forty longitudinal halves of human mandibular premolars were equally divided into 4 groups of 10 samples each: control group (C), samples were stored in distilled water during the experiment period. The remaining 30 specimens were subjected to demineralization protocol to create caries like lesions. samples were immersed for three days in a demineralization solution (pH 5.0) containing 0.2% carbopol and 0.1% lactic acid saturated with calcium phosphate tribasic. The samples were subdivided into 3 equal groups according to the treatment applied during the pH cycle. Demineralization group “D”: no treatment applied. Group “F” treated with 2000 mg/liter sodium fluoride gel. Group “T” treated with 200 mg/liter theobromine gel. The specimens of the two studies groups were subjected to Demineralization- Remineralization PH Cycle Protocol for 5 days (Alternating four steps: 1: Treatment material, fluoride or theobromine ˜= 3 minutes. 2: Demineralizing solution 3 hours. 3: treatment material ˜= 3 minutes. 4: Remineralizing solution till the next cycle). The samples were investigated by scanning electron microscope (SEM) and energy dispersive x-ray analysis (EDXA). Results: The enamel of the demineralization group was porous with artificial caries like changes exposing the subsurface enamel rods with severe rod core defects. Theobromine gel and fluoride gel groups showed marked improvement in the surface characteristics in the enamel in both groups. Theobromine gel group showed more observable enamel surface improvement than the fluoride gel group. EDXA revealed that the calcium-phosphorus ratio displayed a descending order: (C > T > F > D). The differences between the two tested groups were not statistically significant. Conclusion: Theobromine gel had more effective remineralizing potential than fluoride gel as a result of its effect in improving the enamel surface characteristics of human teeth.KeywordsDental caries; Dental enamel, Ultrastructure; Hardness; Microscopy; Electron; Scanning; Sodium Fluoride, Therapeutic use; Theobromine/therapeutic use.